1978
DOI: 10.2105/ajph.68.2.139
|View full text |Cite
|
Sign up to set email alerts
|

The Woodlawn mental health studies: tracking children and families for long-term follow-up.

Abstract: Elementary school children in a large public urban school system (Chicago) can be tracked into adolescence, together with their families, by using student numbers established by the Chicago Public Schools. This paper reports on the linkage between a psychiatric follow-up study and the data bank of the Chicago Public Schools. The authors were able to find information about the location and grade placement of 87 per cent of an urban ghetto neighborhood's first Both longitudinal and cross-sectional, epidemiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Across developmental sub-fields—from basic cognition (e.g., Lauer and Lourenco, 2016) and language development (e.g., Can et al, 2013) to mental (e.g., Agrawal et al, 1978) and physical health (e.g., Fein et al, 2014) to applied interventions targeting children (e.g., Campbell et al, 2012) and their families (e.g., Huston et al, 2005)—researchers are engaging in longitudinal work, re-recruiting families who participated in one study to gain a better understanding of children's developmental trajectories. Frequently, research teams do not decide to begin embarking on this work until several months or years after an original study has concluded.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Across developmental sub-fields—from basic cognition (e.g., Lauer and Lourenco, 2016) and language development (e.g., Can et al, 2013) to mental (e.g., Agrawal et al, 1978) and physical health (e.g., Fein et al, 2014) to applied interventions targeting children (e.g., Campbell et al, 2012) and their families (e.g., Huston et al, 2005)—researchers are engaging in longitudinal work, re-recruiting families who participated in one study to gain a better understanding of children's developmental trajectories. Frequently, research teams do not decide to begin embarking on this work until several months or years after an original study has concluded.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have conducted such longitudinal work across a host of domains, including spatial cognition (e.g., Lauer and Lourenco, 2016), language (e.g., Can et al, 2013), literacy and mathematics achievement (e.g., Krajewski and Schneider, 2009), temperament (e.g., Schwartz et al, 2003), personality (e.g., Harris et al, 2016), memory (e.g., Forman et al, 2011), self-regulation (e.g., Ayduk et al, 2000), health and physical development (e.g., Fein et al, 2014), mental health (e.g., Agrawal et al, 1978), and media use (e.g., Hanson, 2017). Similarly, researchers who evaluate interventions also have engaged in comparable, sometimes non-prospective, longitudinal research years after the conclusion of interventions.…”
Section: Longitudinal Research In Developmental Sciencementioning
confidence: 99%
See 3 more Smart Citations